Mental health street triage: Comparing experiences of delivery across three sites. Issue 1 (15th January 2020) - Callender, Matthew; Knight, Laura J.; Moloney, Daniel; Lugli, Valentina
Accessible summary: What is already known about the topic?: MHST represents transformation at the forefront of policing and mental health to people in crisis with the aim of providing a better and more efficient response. Current knowledge has largely focused on service development, informed by narratives of risk, and this study applies an alternative focus by considering the interplay in practice. What the paper adds to existing knowledge?: This paper adds to emerging work on mental health street triage, offering original insights into the interplay of police officers and mental health nurses in practice. The evidence presented shows how the dynamics between officers and nurses were informed by perceptions of trust, belonging and legitimacy which shaped decision‐making and outcomes. This study also reveals the impacts of leadership continuity and staff turnover to service efficacy and the potential of strategic "drift." What are the implications for practice?: Nurses who work in MHST operations should be prepared to share knowledge, learning and insight into how different mental health conditions present in practice and support the assessment of risk posed to officers. Alternative pathways available to detainment by police under the Mental Health Act should be identified and communicated to officers, both in the control room and in situ, to avoid unnecessary detentions. Strategies should be developed to extend the communication of mental health education and knowledge beyond those immediately involved in MHST to support the police to better respond to mental health. Abstract: Introduction: The limited evidence on mental health street triage (MHST) is largely focused on service development and is overly police‐centric dominated by narratives of risk. This paper considers the interplay between officers and CPNs in practice situated within strategic and operational contexts, illustrating the importance of place to service developments and trust within practice. Aim: This study was conducted to compare the processes, experiences and perceptions of MHST in three sites in England. Method: Semi‐structured interviews were completed with 27 police and health service staff in strategic and operational roles over a three‐month period in three sites in England. Results: Four themes were identified: "Reducing and improving the use of mental health detainments, " "Importance of local contexts and partnerships, " "Enhancing officer confidence" and "Developing street triage." Discussion: Mental health street triage decision‐making and outcomes were influenced by issues of trust, belonging and legitimacy within the interplay between officers and nurses. Continuity and staff turnover influenced strategic and operational development. However, MHST was perceived to be an effective and cost‐saving model. Implications for practice: Mental health nurses are well positioned to lead awareness and education of officers in relation to mental health crisis response. Staff need to develop communication strategies that extend beyond those immediately involved in MHST.